Pelatihan Digital Marketing Dan Branding Produk Dalam Upaya Peningkatan Daya Saing UMKM Di Era Perkembangan Teknologi Maju - Diva Asnia Sabila; Emannuel Alanza Repo; Muhammad Firli Hansdiono; Novi Sari; Sakinah Sakinah (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2025)
The MSME digitalization assistance program in Dusun Nusa Indah aims to enhance the capabilities of local entrepreneurs in utilizing digital technology and artificial intelligence (AI) to strengthen marketing strategies and product competitiveness. This several week program applied a blended learning method combined with intensive mentoring based on the Participatory Rural Appraisal (PRA) approach. A total of 20 MSME actors participated in hands-on training, including product registration on digital platforms and promotional practices through social media. The results show that 60% of participants were able to independently operate digital tools and began using marketplaces and Google Maps to expand their market reach. These findings align with the study by Mansir & Tumin (2022), which emphasizes the role of digitalization in improving MSME marketing performance. Regular evaluations were conducted to ensure program sustainability and responsiveness to dynamic local needs. Thus, this program has proven effective in strengthening the digital capabilities of local MSMEs and supporting inclusive regional economic growth